The application of qualitative research methods to the study of sexually transmitted infections. Issue 2 (1st April 2002) - Power, R
Abstract : Qualitative methods have gained support in health sciences research and have a role to play in STI studies. This article reviews the main techniques used by qualitative researchers, with illustrations taken from the field of STIs.